Harmonizing Cultural Literacy and Empowerment: A Community Education Approach through Angklung Public Class - Sri Nurhayati; Islami Dina; Gumpanat Boriboon; Udeme Samuel Jacob (Universitas Muhammadiyah Mataram, 2024)
This research investigates the preservation of cultural heritage through community-based music education, focusing on the Angklung public class in Indonesia. Its primary purpose is to analyze how the program enhances cultural literacy and empowers participants. Using a qualitative case study methodology, data were gathered through semi-structured interviews, supported by observational checklists and document analysis, and subjected to thematic analysis. The findings highlight substantial cultural literacy improvement, including understanding the cultural significance of Angklung, integrating historical narratives, and exploring traditional and modern repertoires. Participants reported empowerment through community support, flexible learning environments, and mastery of traditional music skills. Social engagement and community cohesion emerged as vital to sustaining participation. These findings underscore the value of adaptive, culturally immersive, and community-centered educational models. The study suggests practical applications for shaping policies and practices in cultural education to ensure the continuity of traditional arts in contemporary society.